Integrated Management of Sclerotinia Sclerotiorum, An Emerging Fungal Pathogen Causing White Mold Disease - Md. Iqbal, Faruk (Journal of Plant Cell Development, 2022)
Sclerotiniasclerotiorum, the causal agent for white mold (Sclerotinia stem rot), is a devastating fungal pathogen. Currently, Sclerotinia is most commonly managed using the chemical fungicide which can lead to Sclerotinia resistance development, impacting biodiversity and interfering with key ecosystem services. In this regards, field experiments were conducted during 2017-18 planting seasons to evaluate the efficacy of different components viz. sawdust burning, stable bleaching powder, fungal and bacterial bio-control agents, chemical fungicide Rovral 50 WP and integration of different components for the management white mold disease of bush bean, mustard and garden pea in three different locations viz. in the field of Plant Pathology Division, Bangladesh Agricultural Research Institute, Joydebpur, Gazipur, Regional Agricultural Research Station (RARS), Burirhat, Rangpur and RARS, Ishurdi, Pabna, respectively. The results showed that different treatments displayed varying levels of effectiveness against the disease. All the treatments gave satisfactory reduction of white mold disease development and increased plant growth as well as yield of bush bean, mustard and garden pea. Among the treatments, integration of saw dust burning + soil amendments with Trichoderma based bio-fungicide + bacillus based bio-control agents + application fungicide Rovral 50 WP is the best treatment which reduced 97.49%, 77.72%, 72.26% white mold disease incidence and 84.61%, 81.14%, 71.01% white mold disease severity of mustard, bush bean and garden pea, respectively and increasing plant growth parameter as well as 52.16%, 27.74%, 36.97% yield of mustard, bush bean and garden pea, respectively. Application of only fungicide Rovral 50 WP also better treatment in reduction of white mold disease incidence and disease severity and increasing plant growth parameter as well as increasing yield of mustard, bush bean and garden pea. Soil amendment with fungal or bacterial bio-control agents also gave satisfactory results in reduction of white mold disease incidence and disease severity and increasing plant growth parameter as well as increasing yield of mustard, bush bean and garden pea. It could be concluded from the obtained results that integration between bio-control agents as a soil treatment and foliar application chemical fungicide might be useful as a good tool for controlling white mold disease caused by S.sclerotiorum and obtained higher yield of bush bean, mustard and garden pea under field condition.
Keywords: Sclerotinia sclerotiorum¸ white mold; bush bean; mustard; garden pea; bio-control agents; Rovral